Notes on the Social Study of Collective Sensibilities through Music - Scribano, Adrián Oscar (2015)
The sociological research on bodies, emotions and expressiveness provides us an opportunity to recognize creative ways connected to music as a source for the social phenomena analysis. Our goals in this article are twofold: a) explore the connections between social research, creativity and a social studies approach to bodies/emotions and b) explain how this can be an effective and efficient strategy in the development of a doctoral dissertation. This paper is divided into two main sections. The first is a review of the literature on a panoramic consideration of Art Based Research as methodological strategy of our work, and a theoretical exploration of the emotions/bodies from a sociological perspective. The second main section presents a description of reggae music in San Andrés Island as part of doctoral research. It seeks to analyze the relation between musical practice and the social rhythms that open the way to cultural resistance and alternative emotional tuning. Our argumentation tries to highlight how creativity allows us to explore ways to be more autonomous social scientists and help us to listen -with more flexibility- to the people that make part in our studies.